A PUF-Based Modeling-Attack Resilient Authentication Protocol for IoT Devices - Ebrahimabadi, Mohammad; Younis, Mohamed; Karimi, Naghmeh (IEEE, 2021)
Physical Unclonable Functions (PUFs) offer a promising solution for authentication of IoT devices as they provide unique fingerprints for the underlying devices through their challenge-response pairs. However, PUFs have been shown to be vulnerable to modeling attacks. In this paper, we propose a novel protocol to thwart such vulnerability by limiting the adversary’s ability to intercept the whole challenge bits exchanged with IoT nodes. We split the challenge bits over multiple messages and engage one or multiple helper nodes in the dissemination process. We further study the implications of various parts of the challenge patterns on the modeling attack and propose extensions of our protocol that exploit bits scrambling and padding to ameliorate the attack resiliency. The experimental results extracted from a 16-bit and a 64-bit arbiter-PUF implemented on FPGA demonstrate the effectiveness of the proposed methods in boosting the robustness of IoT authentication.